2019
DOI: 10.1002/jcp.28112
|View full text |Cite
|
Sign up to set email alerts
|

The role of arsenic in obesity and diabetes

Abstract: As many individuals worlwide are exposed to arsenic, it is necessary to unravel the role of arsenic in the risk of obesity and diabetes. Therefore, the present study reviewed the effects of arsenic exposure on the risk and potential etiologic mechanisms of obesity and diabetes. It has been suggested that inflammation, oxidative stress, and apoptosis contribute to the pathogenesis of arsenic‐induced diabetes and obesity. Though arsenic is known to cause diabetes through different mechanisms, the role of adipose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(31 citation statements)
references
References 102 publications
(186 reference statements)
2
25
1
Order By: Relevance
“…These diseases may also provide an additional link between COVID-19 severity and heavy metal toxicity. Earlier data demonstrate that obesity and diabetes may be associated with Hg ( Tinkov et al, 2015 ; Roy et al, 2017 ), Сd ( Satarug et al, 2010 ; Tinkov et al, 2017 ), Pb ( Park et al, 2017 ; Leff et al, 2017 ), and As ( Farkhondeh et al, 2019 ). Although these associations are rather contradictory and the underlying mechanisms are still unclear, it is proposed that the role of metals and endocrine disruptors may significantly contribute to metabolic disorders.…”
Section: Introductionmentioning
confidence: 99%
“…These diseases may also provide an additional link between COVID-19 severity and heavy metal toxicity. Earlier data demonstrate that obesity and diabetes may be associated with Hg ( Tinkov et al, 2015 ; Roy et al, 2017 ), Сd ( Satarug et al, 2010 ; Tinkov et al, 2017 ), Pb ( Park et al, 2017 ; Leff et al, 2017 ), and As ( Farkhondeh et al, 2019 ). Although these associations are rather contradictory and the underlying mechanisms are still unclear, it is proposed that the role of metals and endocrine disruptors may significantly contribute to metabolic disorders.…”
Section: Introductionmentioning
confidence: 99%
“…The increased concentration of oxidative molecules, known as oxidative stress may lead to the enhanced incidence rate of damages in lipids, proteins, and genetic material. 59,60 Brb has shown great potential in attenuation of oxidative stress. Jiang et al used human melanocyte cell line which was induced oxidative stress using PIG1 and H 2 O 2 .…”
Section: Mediated By Nrf2 Signaling Pathwaymentioning
confidence: 99%
“…Arsenic inhibits adipogenesis and enhances lipolysis, leading to obesity. Other reports have suggested that arsenic may induce lipodystrophy [193]. Another evidence suggests that uremic toxin-treated 3T3-L1 cells and MSC-derived adipocytes exhibit impaired adipogenesis and apoptosis through activation of the Na/K-ATPase/ROS amplification cycle [194].…”
Section: Environmental Factorsmentioning
confidence: 97%
“…In addition to PBDEs, evidence linking accumulation of other persistent organic pollutants (POPs) and risk of IR and T2DM was previously described [54,192]. Additionally, the association between inorganic arsenic exposure and the risk of T2DM and obesity was previously reported [193]. Arsenic-induced T2DM is suggested to be mediated by inflammation, oxidative stress, and apoptosis, playing a significant role in the pathogenesis of obesity.…”
Section: Environmental Factorsmentioning
confidence: 99%